Review of information systems research for media industry–recent advances, challenges, and introduction of information systems research in the media industry - Lugmayr, Artur; Grueblbauer, J. (2017)
Global media reports clearly show a tremendous increase in spending on Information Technology (IT) and Information Systems (IS) in the media sector. Two main trends are currently visible. First, as stated in McKinsey & Company’s Global Media Report, consumers continuously shift from spending on traditional media products towards rapidly-increasing spending on digital services and media products – consumer patterns have rapidly changed. Second, as stated in Gartner’s reports about the media industry, spending on IT services in the media industry increases gradually, and as a whole, the media industry is the third-largest spender on IT, after banking/finance and manufacturing. Third, as reported by both authors in their works, several facets of the media industry have undergone extreme changes, including business models, declining revenue, content models, management, economics and public funding. The aim of this study is to investigate research work related to IS in the media industry, in particular in the management and economic areas. To conduct this study, we investigated a large corpus of studies that have been contributed to IS research within the Association for Information Systems (AIS) within the past decades. We utilised advanced text mining methods to identify contributions and thematic areas. Our results clearly indicate that there is a significant downward trend of research works dealing with media industry aspects. This trend was a surprise to us, as it contradicts the emergence of new digital technologies which became key drivers in the media industry after 2009. We conclude this article by giving research directions, illustrating the opportunities and importance of investigating media industries within the context of IS, and introducing the research field of Information Systems in the eMedia Industry.